2021
DOI: 10.1051/ctv/ctv2021360145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cost-effectiveness of grid-connected photovoltaic solar energy in wineries

Abstract: The objective of this study was to analyze the cost-effectiveness of photovoltaic (PV) solar energy in wineries. The factors analysed were solar radiation, cost of PV installation, prices in the public electricity grid, size of the winery, power of installed panels, influence of the decreased consumption during weekends, and seasonality in the consumption. The study has been based on the European TESLA project, in which 39 energy audits were carried out in wineries in four European countries. A winery of 30,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…In industries with relatively constant demand throughout the year, the implementation of Photovoltaic (PV) could be a solution, as shown in previous studies [18]. The constant demand pattern allows the energy generated by PV to be used throughout the year, leading to greater profitability.…”
Section: Impact Of the Electricity Price Increase Experienced So Far ...mentioning
confidence: 98%
“…In industries with relatively constant demand throughout the year, the implementation of Photovoltaic (PV) could be a solution, as shown in previous studies [18]. The constant demand pattern allows the energy generated by PV to be used throughout the year, leading to greater profitability.…”
Section: Impact Of the Electricity Price Increase Experienced So Far ...mentioning
confidence: 98%
“…For example, Jimenez-Castillo et al [10] demonstrated the importance of optimizing the orientation and inclination in olive mills, based on the uniqueness of its consumption pattern, adapting it to seasonality. In wineries, seasonality was key in the profitability of the system for self-consumption, related to the optimum power to be installed in PVs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Algunas investigaciones demuestran el impacto de la optimización de la envolvente de edificios industriales Bovo, M;Torreggiani, D;. Otra estrategia para reducir los costos energéticos en el sector industrial de bodegas la constituye la generación de energía solar (Perdigones, A;2021). Por otro lado, diagnósticos energéticos realizados en San Juan en el marco del Programa de Eficiencia Energética del Consejo Federal de Inversiones a bodegas de elaboración y conservación en el año 2020-2021, proponen usualmente la incorporación de generadores fotovoltaicos como mejora, basándose en la magnitud del recurso solar que caracteriza la zona.…”
Section: Introductionunclassified